Aesthetics of Jaran Ukir Decorating Tempel Technique of Kasongan Village Pottery - Suharson, Arif; Fitriani, Dyah Retno; Ridho, Awang (Institut Seni Indonesia Denpasar, 2025)
This research aims to create a new creation carved with the characteristic of tempel technique decoration, which is the strength of the local genius of Kasongan Village pottery that meets the quality standards of raw materials and modern design. Other regions do not own the tempel technique decoration that characterizes Kasongan Village pottery. However, its existence is starting to recede, with poor regeneration, and is no longer to the needs of the times. Direct hand-building pottery products with tempel technique decorations are complicated, difficult, and old-fashioned. The younger generation prefers to make printed pottery products that are considered more practical to be created with fabricated paint finishing according to global tastes while ignoring the local identity of Kasongan Village pottery characteristics. This research uses aesthetic methods with a practice-based research approach carried out with the stages of literature research, empiric study, visual research, and practice. The aesthetics of the new Kasongan carving, with the application of the tempel decoration technique, impact the preservation of sustainable local artistic creations. Creating a new carving with the tempel technique decoration in Kasongan Village is expected to be an educational tool for learning about the character of the nation's next generation from an environmental and cultural perspective. Carving with tempel technique decoration is an entity that must be maintained, preserved, and developed according to the global community's needs.